ENHANCING RELIGIOUS TOURISM THROUGH HALAL CERTIFICATION AND CREATIVE PACKAGING: AN ASSET-BASED COMMUNITY DEVELOPMENT PERSPECTIVE - Ahyadi; Kurniawati, Dita; Niam, Khoirun; Arifin, Zaenal; Ahmad, Andi (International Journal of Cultural and Social Science, 2026)
This study empirically examines the effectiveness of an integrated empowerment program that combines halal certification assistance and creative packaging design to enhance the competitiveness of MSMEs in the religious tourism area of the Great Mosque of Demak, Central Java. Using an Asset-Based Community Development (ABCD) approach, the program involved participatory asset mapping, facilitation of halal certification in collaboration with BPJPH and a local Islamic higher education institution, Islamic-themed packaging design training, and sharia-compliant digital marketing assistance. A descriptive–evaluative design was employed with quantitative and qualitative data collected before and after the intervention. The results show that all 15 MSMEs obtained halal certification, adopted redesigned packaging that reflects local Islamic identity, and achieved an average sales increase of about 52% within three months. Qualitative evidence indicates improved halal literacy, stronger product identity, and greater market confidence. The study concludes that integrating halal certification and packaging innovation through an asset-based approach can effectively strengthen MSME competitiveness in religious tourism destinations.